416 RHEUMATOID ARTHRITIS-SPECIFIC AUTOANTIBODIES ARE PRESENT IN PATIENTS WITH INTERSTITIAL LUNG DISEASE IN THE ABSENCE OF ARTHRITIS. Issue 1 (1st January 2007) - Gizinski, A. M.; Kervitsky, D.; Meehan, R.; Brown, K. K.; Holers, V. M.; Deane, K. D.
Abstract : Purpose: To identify rheumatoid arthritis (RA)-related anti-cyclic citrullinated peptide (anti-CCP) in patients with interstitial lung disease (ILD) and no clinical evidence of connective tissue disease, supporting the hypothesis that RA-related autoimmunity may develop in the lung prior to arthritis. Methods: This was a cross-sectional descriptive study using a database of subjects with known ILD who had undergone a standardized evaluation. Twelve subjects were identified with an idiopathic ILD and a positive rheumatoid factor in whom anti-CCP testing had been performed. For these subjects, the following data were abstracted: pulmonary diagnosis, gender, smoking status, age at diagnosis of ILD, joint examination findings, and results of anti-CCP antibodies testing. An RF was considered positive if > 20 IU/mL and anti-CCP positive if > 20 units/mL. Results: None of the 12 patients had synovitis or other diagnostic criteria for connective tissue disease. Five were positive for anti-CCP antibodies; of these, four had idiopathic pulmonary fibrosis (IPF) and one idiopathic nonspecific interstitial pneumonia (NSIP). Seven cases were anti-CCP negative, with five cases of IPF and two cases of NSIP. Four of the five CCP/RF positive patients were smokers. Although not statistically significant, smoking was associated with increased risk of anti-CCP positivity (OR 3). One patient with RF/CCP positivity developed clinically apparent synovitis 2 years after diagnosis of the lung disease; the other anti-CCP/RF positive subjects did not develop synovitis over 1 to 5 years of follow-up. Conclusions: Positive anti-CCP antibody can occur in the setting of an otherwise idiopathic ILD. Given the high specificity of anti-CCP for RA (> 98%), this suggests that the five patients with both RF and anti-CCP positivity are at high risk for the development of RA-specific joint disease. In addition, four of these patients were active smokers at the time of ILD diagnosis. These findings are intriguing and imply, as recent work also suggests, that RA-specific immune dysregulation may initially occur in the lung and may be related to tobacco use. Further studies are needed to establish the longitudinal course of patients with anti-CCP positivity and ILD in the absence of synovitis, as well as the relationship between genetics, environmental exposures, citrullination, and the lung as the site of initiation of RA-specific humoral immunity.